SOURCE ROCK CHARACTERIZATION AND CORRELATION IN JAMBI SUBBASIN, SOUTH SUMATRA BASIN BASED ON GEOCHEMICAL METHOD - Nadya Shafira, Aiko
Geologically, the research area is located in Jambi Subbasin, South Sumatra Basin. In general, source rocks and oils sample were taken from five exploration wells. Geochemical analysis through LECO, Rock-Eval pyrolisis, and vitrinite reflectance was conducted on 152 source rock samples then validated to 31 source rock samples to determine the quantity, quality, and maturity of organic material in each formation. Biomarker analysis using normal alkane, isoprenoid, sterane, and terpane as parameter also isotop data analysis was conducted on six source rock samples, one condensate sample, and one oil sample to determine the origin of organic material, depositional environment, also correlation between oil and condensate, oil and source rock, also condensate and source rock. The result of geochemical analysis shows that Talangakar Formation is categorized as effective source rock. The result of biomarker analysis shows that the oil and condensate sample are not correlated. The oil sample is positively correlated with source rock from Talangakar Formation which is deposited in transitional to terrestrial environment. The condensate sample that originated from shallow marine is negatively correlated with all source rock. It is indicated to have originated from another source rock sample of Baturaja Formation that is not collected in this research.